Caracterização funcional de proteases e inibidores do carrapato rhipicephalus microplus e do parasita babesia bovis - Lu, Stephen [UNIFESP] (2019)
Objectives: Functional characterization of a subtilisin-like serine peptidase, an aspartic peptidase and a cysteine peptidase from Babesia bovis parasites and characterization of a novel type 1 cystatin inhibitor from the tick Rhipicephalus microplus. Material and methods: We searched the B. bovis genome and selected three peptidases: a subtilisin-like peptidase (XP_001610126) (BbSp), an aspartic peptidase (BBOV_IV007890) (BbAsp) and a cysteine peptidase (XP_001612131) (BbCp). The recombinant protein was obtained using different expression systems (bacteria, yeast or insect cells) and purified. The recombinant proteins were injected in rabbits or mice to produce antibodies that were used in B. bovis in vitro neutralization assays. After refolding the recombinant BbCp presented proteolytic activity and, for that reason, we carried out its biochemical characterization and substrate profiling using a peptide library in phage display. We also investigated its proteolytic activity in the presence of different inhibitors, including cystatins from R. microplus. At the same time, we cloned, expressed, purified and characterized a novel type 1 cystatin from the tick R. microplus. Results: Initially BbSp expression assays were performed in bacteria, yeast and insect cells, however, the recombinant protein was not detected in the condition tested. Therefore, a predicted immunogenic N-terminal region of BbSp was selected and expressed in bacteria. Antibodies anti-BbSp N-terminal region impaired B. bovis growth in vitro and a reduction of 32% in infected cells was observed. Simultaneously, recombinant BbAsp was produced using insect cell expression system and antibodies anti-BbAsp reduced the parasitemia in 61% compared to the control groups. Finally, recombinant BbCp was obtained in bacterial inclusion bodies and became soluble only in the presence of urea 8M. After purification recombinant BbCp present itself as a 37 kDa protein band and after refolding as a 25 kDa protein band. As other cysteine peptidases, BbCp proteolytic activity was enhanced in the presence of a reducing agent (DTT), had an optimum pH between 6.5 – 7.0, had preference for Ser>Pro>Val>Leu>Phe at P2 position and was completely inhibited by E64. Moreover BbCp was also inhibited by R. microplus cystatins, such as Bmcystatin-1 (Ki = 2.89 nM) and Rmcystatin-3 (Ki = 0,13 nM). Antibodies anti-BbCp impaired B. bovis growth in vitro xxi and a reduction of 32% of infected cells was observed. In collaboration with the Instituto de Pesquisas Veterinárias Desidério we analyzed the modulation of 4 cystatin genes in the midgut of R. microplus infected with B. bovis and the cystatins Bmcystatin-1, Rmcystatin-1b and Rmcystatin-3 appeared to be modulated. Rmcystatin-1b transcripts were mainly found in the midgut of partially (65 times higher in relation to salivary glands) and fully (40 times higher in relation to hemocytes) fed R. microplus females. Moreover, Rmcystatin-1b transcripts were found down-modulated during the first three days post-detachment. The recombinant inhibitor was obtained in bacteria and presented inhibitory activity towards several cysteine peptidases, such as BmCL-1 (Ki = 0.013 nM), papain (Ki = 0.72 nM), human cathepsin L (Ki = 0.41 nM), human cathepsin B (Ki = 0.27 nM) and recombinant BbCp (Ki = 7,48 nM). Rmcystatin-1b was also able to partially inhibit proteolytic activity of R. microplus midgut extracts 48 hours postdetachment. Moreover, the recombinant inhibitor also impaired B. bovis growth in vitro and a reduction of 50% was observed 72 hours post-treatment. Conclusion: Despite the several conditions tested we were unable to obtain an active recombinant BbSp and BbAsp. Meanwhile, recombinant BbCp displayed typical cysteine peptidase kinetic features. The neutralization assays carried out with antibodies against the selected peptidases suggest their possible role during parasite invasion/egress of bovine erythrocytes. Rmcystatin-1b was mainly localized in tick midgut and the severe down-modulation during the first days post-detachment together with its ability to inhibit native cysteine peptidase from R. microplus midgut suggest its role as a possible regulator of R. microplus digestion. Moreover, since the recombinant inhibitor was able to inhibit B. bovis cysteine peptidase and interfered with parasite growth in vitro, we speculate that interplay between B. bovis peptidase and R. microplus inhibitors may contribute to parasite control and survival in the tick.